2022
DOI: 10.3390/ijerph19148683
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of High-Porosity B-TiO2/C3N4 Composite Materials: Adsorption–Degradation Capacity and Photo-Regeneration Properties

Abstract: Adsorption can quickly remove pollutants in water, while photocatalysis can effectively decompose organic matter. B-TiO2/g-C3N4 ternary composite photocatalytic materials were prepared by molten method, and their adsorption–degradation capability under visible light conditions was discussed. The morphology of the B-TiO2/g-C3N4 materials was inspected by SEM, TEM, BET, and EDS, and the results showed that close interfacial connections between TiO2 and g-C3N4, which are favorable for charge transfer between thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The results were applied to further reveal the mechanism of AT@PbS photocatalytic degradation of MB. It was generally believed that [ 37 , 38 ], EDTA-2Na was a hole-trapping agent, TBA was considered to be a hydroxyl radical trapping agent, CCl 4 was believed to be an electron trapping agent, and BQ was deemed an oxygen radical trapping agent. It is obvious from the results in Figure 11 a that the effects of EDTA-2Na and TBA on MB degradation efficiencies were much greater than those of BQ and CCl 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The results were applied to further reveal the mechanism of AT@PbS photocatalytic degradation of MB. It was generally believed that [ 37 , 38 ], EDTA-2Na was a hole-trapping agent, TBA was considered to be a hydroxyl radical trapping agent, CCl 4 was believed to be an electron trapping agent, and BQ was deemed an oxygen radical trapping agent. It is obvious from the results in Figure 11 a that the effects of EDTA-2Na and TBA on MB degradation efficiencies were much greater than those of BQ and CCl 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Photocatalytic oxidation takes advantage of the strong oxidation capacity of the photocatalyst oxidant to open the ring and remove nitrogen, before finally realizing complete mineralization, making it lose toxicity without secondary pollution. Among them, TiO 2 has become a research hotspot of photocatalysts due to its high chemical stability, non-toxic, low cost and other advantages, and its photostability and efficiency are highly favored [ 13 , 14 , 15 , 16 , 17 ]. Ortega Liébana et al found that 3-chloropyridine was completely mineralized under TiO 2 photocatalysis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%